The Uncertain Sound of the Trumpet: Catholic Values and Medical Sociology - Curtis, Jack H. (The American catholic sociological review, 1961)
Medicine and psychiatry are among those disciplines which are growing in their appreciation of sociology. The now established field of medical sociology has already revealed some important social aspects of health. Catholic sociologists are potential recruits for medical sociology because concern for human well-being ranks at the top of their value system. The American sociologist has been hampered in his approach to world health by his middle-class orientation. Catholics, because of their hierarchy of values are able to transcend this middle-class orientation and should lead the way toward a more humanity-wide medical sociology.